Understanding organizations : theories & images - Staber, Udo H. (SAGE, 2013)
"Understanding Organizations: Theories and Images introduces students to the key principles of understanding, designing, and managing organizations in an accessible and practical way. The book provides a conceptual toolkit containing the essential models, theories and concepts needed for working in, managing and evaluating organizations. Key Features: Insightful anecdotes discuss how for- and not-for profit organizations fit within our current society from a social and economic perspective ; Theoretical framework and multi-perspective approach focuses on economics, institutionalism and evolution theory highlighting the relationship between organizations, employees and the broader society ; Research-focused approach analyses organizational phenomena in light of recent studies. This textbook is ideal for undergraduates and postgraduates studying general management, organizational theory, organizational design, and organizational sociology."--Publisher's website.